Soaring High Into The Blue Sky-AirAsia, The First Low-Fares, No-Frills Airline In Malaysia - May, Leong Chuay (2003)
This case study will take a closer look at the low-fares, no frills concept and find out how it differs from the conventional full-service carrier. It will further uncover the secret behind AirAsia's success and explore the future strategies for AirAsia to win the competition and achieve competitive advantage.